Saudi Society Of Colon And Rectal Surgery (SSCRS) Position statement on colorectal surgery and endoscopy during the COVID-19 pandemic - Reem A. Alharbi; Moneera Y. Binsaleem; Ohoud M. Alamodi; Ahmed A. Alkhamis; Bader H. Alshaban; Noura S. Alhassan; Sara I. Albastaki; Khayal A. Alkhayal; Omar A. Alobeed; Ahmad M. Zubaidi; Khalid A. Alresini; Samar J. Alhomoud; et al. (World Journal of Colorectal Surgery)
The coronavirus disease 2019 (COVID-19) pandemic has vastly impacted normal day-to-day surgical practice throughout the world. It is an infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The treatment of colorectal diseases in the presence of COVID-19 infections must be reconsidered. An expert's panel from the Saudi Chapter and Gulf Cooperation Council Countries Chapter under the umbrella of the Saudi Society of Colon and Rectal Surgery was assembled. The panel identified the key questions and systematically reviewed all reports around the impact of COVID-19 on colorectal cancer treatment, emergency surgery, surgical technique, endoscopy, and operating room protocols. Using the grading of recommendations assessment, development, and evaluation (GRADE) methodology and the evidence-to-decision framework, the strength of recommendations and the quality of evidence were determined by the panel. The panel recommends a thorough review of current surgical practice in the field of colorectal diseases to minimize the impact of COVID-19. Lack of clinical trials and local regional data in the area of colorectal diseases during the COVID-19 pandemic are marked as limitations of this study.